2014
DOI: 10.1586/17476348.2015.992783
|View full text |Cite
|
Sign up to set email alerts
|

The role of prostaglandins in allergic lung inflammation and asthma

Abstract: Prostaglandins are products of the cyclooxygenase pathway of arachidonic acid metabolism. There are five primary prostaglandins, PGD2, PGE2, PGF2, PGI2, and thromboxane B2, all of which signal through distinct seven transmembrane, G-protein coupled receptors. Some prostaglandins may counteract the actions of others, or even the same prostaglandin may have opposing physiologic or immunologic effects, depending on the specific receptor through which it signals. In this review, we will examine the effects of cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 190 publications
(246 reference statements)
1
91
0
7
Order By: Relevance
“…PGI 2 has a well-established correlation to allergic disorders, as several studies in mice have shown that PGI 2 administration diminishes features of allergic and asthmatic airways including airway eosinophilia, Th2 cytokine production, and AHR, while PGI 2 signaling deficiency leads to exaggerated allergic inflammation [51][52][53][54]. In addition, it has been shown that PGI 2 levels are elevated in the lungs of individuals during allergic inflammation, which demonstrates that PGI 2 is present during allergic inflammation in humans [26]. Therefore, PGI 2 is considered an important player in the regulation and dampening of Th2 inflammation.…”
Section: Prostaglandin I 2 (Pgi 2 )mentioning
confidence: 95%
See 3 more Smart Citations
“…PGI 2 has a well-established correlation to allergic disorders, as several studies in mice have shown that PGI 2 administration diminishes features of allergic and asthmatic airways including airway eosinophilia, Th2 cytokine production, and AHR, while PGI 2 signaling deficiency leads to exaggerated allergic inflammation [51][52][53][54]. In addition, it has been shown that PGI 2 levels are elevated in the lungs of individuals during allergic inflammation, which demonstrates that PGI 2 is present during allergic inflammation in humans [26]. Therefore, PGI 2 is considered an important player in the regulation and dampening of Th2 inflammation.…”
Section: Prostaglandin I 2 (Pgi 2 )mentioning
confidence: 95%
“…Eicosanoids have long since been associated with Th2 inflammatory diseases and share a common origin, from arachidonic acid [25][26][27]. Arachidonic acid can be metabolized into downstream prostaglandins by the cyclooxygenase enzymes, COX-1 and COX-2, and to leukotrienes by the 5-lipoxygenase enzyme.…”
Section: Lipid Mediator Activation Of Ilc2mentioning
confidence: 99%
See 2 more Smart Citations
“…Prostaglandins have a variety of physiological and immunological effects [53,54]. PGE2 in particular supports phagocyte-mediated inflammation but can also skew type 1 into type 2 immune responses or enhance immunosuppressive activity of Treg and MDSC [55].…”
Section: Msc Immunosuppressive Properties In Vivomentioning
confidence: 99%